Apparent Bicarbonate Uptake and Possible Plasmalemma Proton Efflux in Chara corallina - Ferrier, Jack M. (1980)
It is shown that the apparent uptake of bicarbonate by cells of Chara corallina could be the result of a proton efflux coupled to extracellular production of CO(2) from bicarbonate, with CO(2) being taken up by the cell. The theoretical results presented here show that the influx of CO(2) across the plasmalemma can be much greater than previously thought, if there is a large efflux of protons across the plasmalemma, and that, if this occurs, there would be a much steeper gradient of pH near the cell surface than previously thought possible.